THE PLACE OF ARTIFICIAL INTELLIGENCE (AI) IN THE TEACHING PROFESSION IN THE 21ST CENTURY. (Scientific Journal of Educational Management, Research and law, 2025)
The study was carried out to examine how the Artificial Intelligence (AI) program can enhance the teaching profession in Nsukka Education Zone of Enugu State. Two research questions and two null hypotheses tested at 0.05 level of significance guided the study. The study adopted descriptive survey design. The population of the study was 221 comprising of 88 male teachers and 133 female teachers. There was no sampling as the population is manageable. The instrument for data collection was a questionnaire developed by the researchers titled “Enhancing Teaching Profession through Artificial Intelligence (ETPTAI).” The instrument was validated by three experts. The reliability of the instrument was 0.73 derived using Cronbach Alpha Statistics. Data collected were analyzed using Mean and Standard Deviation to answer the research questions, while t-test was used to test the hypotheses. Result of the data analysis revealed that the use of AI program to a high extent enhance the teaching profession, as global access to quality education has been greatly enhanced with the use of artificial intelligence programs such as smartphone and internet connections which gives access to education tools and information that makes and keeps one educated. Based on the findings, it was recommended among others that both teachers and learners must grapple with and acquire training on ethical AI technology usage for the enhancement of the teaching profession.